ANALYSE DES BESOINS EN FOS : ETUDE DE CAS DES ÉTUDIANTS DU TOURISME ET DE L’HÔTELLERIE EN JORDANIE - Nisreen Abu Hanak (European Scientific Journal, ESJ, 2014)
The objective of this research is to analyze the needs of Jordanian students majoring in the field of Tourism and Hotel Management regarding their professional specific training in French. In deed, the analysis of the results of a questionnaire carried out with the help of those students enabled the researcher to list their needs. These results led the researcher to provide pedagogical solutions that suit this public through proposing a module of tourism that focuses on the development of professional skills of students in relation to their fields.